Superiority illusion in older adults: Volume and functional connectivity of the precuneus - Yuki Shidei; Daisuke Matsuyoshi; Ayako Isato; Genichi Sugihara; Hidehiko Takahashi; Makiko Yamada (PCN Reports)
Abstract Aim Superiority illusion (SI), a cognitive bias where individuals perceive themselves as better than others, may serve as a psychological mechanism that contributes to well‐being and resilience in older adults. However, the specific neural basis of SI in elderly populations remains underexplored. This study aims to identify brain regions partially associated with SI, exploring its potential role in adaptive psychological processes. Methods This study combined a behavioral task, voxel‐based morphometry (VBM), and resting‐state functional connectivity (rsFC) analyses to investigate the neural substrates of the SI in a cohort of 145 participants, including young (n = 84), middle‐aged (n = 37), and older adults (n = 24). Results Our findings indicated that higher SI scores in older adults were correlated with greater gray matter volume in the right precuneus and stronger rsFC between the right precuneus and the left lateral occipital cortex. However, these correlations were not evident in younger and middle‐aged groups. Conclusion Our findings underscore the importance of the right precuneus and its connectivity in the manifestation of the SI, particularly in older adults, highlighting its potential role in adaptive aging processes.